Physiotherapy improves symptoms of exercise-induced laryngeal obstruction in young elite athletes: a case series - Kolnes, L.-J.; Vollsæter, M.; Drange Røksund, O.; Stensrud, T. (BMJ Open Sport & Exercise Medicine, 2019)
Objective A constricted, upper chest breathing pattern and postural dealignments habitually accompany exercise-induced laryngeal obstruction (EILO), but there are few effective treatments for athletes presenting with EILO. This case series was conducted to examine whether physiotherapy based on principles from the Norwegian psychomotor physiotherapy (NPMP) combined with elements of cognitive behavioural therapy can reduce laryngeal distress in athletes with EILO.